EFFECTS OF SUSTAINABLE LEADERSHIP STYLES ON STUDENTS' SUCCESS: A STUDY OF QATAR’S UNIVERSITIES - Muhammad Jehanzaib Chaudhry, Dr. Jamilah Binti Ahmed, Sadia Noureen (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Present study aims to discuss the effects of sustainable leadership styles on student’s success. In order to investigate the data was collected from secondary sources and previous studies. Difficulties Faced for Sustainability Leadership is discussed. Major issues have been highlighted which hinders student’s success.